ARTIFICIAL INTELLIGENCE IN AGRICULTURE: THE IMPACT ON LABOR PRODUCTIVITY - Soldić Aleksić, Jasna; Zečević, Aleksandra; Chroneos Krasavac, Biljana (Economics of Agriculture, 2024)
The last few years have seen the artificial intelligence technologies’ potential to radically transform many industries, including agriculture, by optimizing the use of resources, increasing productivity, work efficiency, and resistance to climate change. The basic research question here is the degree of connection between the level of productivity in agriculture, on the one hand, and the degree of acceptance of AI technologies and a number of agriculture-related economic indicators, on the other hand. For this purpose, an empirical data analysis was carried out for EU 27 member countries. The results of the analysis show a moderately strong positive relationship between the level of the Labor Productivity in Agriculture and the AI Readiness Index score. Also, there is a statistically significant, but slightly less pronounced, positive relationship between the level of the Labor Productivity in Agriculture and GDP per capita and Agriculture, Forestry, and Fishing, Value Added (current US$) in Millions.